Assessing the Effectiveness of the Village Court (VC) System in Promoting Access to Justice: A Case Study of Two Selected Villages in Noakhali, Bangladesh - Badsha Mia; Seefat E Mannan; Anil Kuman Shrestha (Daengku: Journal of Humanities and Social Sciences Innovation, 2023)
This study aimed to assess the effectiveness of the Village Court (VC) system in promoting access to justice in rural Bangladesh. The formal legal system in Bangladesh is expensive and time-consuming, making it difficult for underprivileged rural people to access justice. The VC system is a combination of formal and informal dispute resolution processes and has been initiated by the government to address the demand for access to justice for rural people. However, several obstacles have hampered the efficacy of the VC system, making it impossible to acquire public satisfaction in the justice process. This case study examines the effectiveness of the village court system in promoting access to justice in two selected villages in Noakhali district, Bangladesh. The study evaluates various factors that impact the success of the village court system, such as policies, procedures, acts, rules, oversight mechanisms, legal awareness, and resources available to Union Parishad officials and community members. The findings suggest that while the village court system is functional in some areas, it heavily relies on government-supported projects and is largely ineffective outside of these areas. The study provides recommendations for improving the effectiveness of the village court system, including necessary amendments to the village court act/rules, proper government monitoring and supervision, improved financial and human resources for the Union Parishad, and greater accountability and competency of all stakeholders. By addressing these issues, the village court system could become a vital tool for promoting access to justice in rural Bangladesh.